PEMEX : the ethanol decision - Corrales Estrada, Martha, (SAGE Knowledge. Cases., 2017)
In the early 2000s, the Federal government of Mexico enacted a series of laws promoting the use of alternative fuels in gasoline, beginning with ethanol from sugarcane. This meant that the national oil company PEMEX had to find ways to implement this policy. Nevertheless, in spite of efforts by various government agencies as well as PEMEX, by mid-2014 no ethanol had been incorporated into Mexicos gasoline supply.